2019
DOI: 10.23919/saiee.2019.8643145
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Monitoring of Leakage Current on Composite and Glass Insulators of the Cahora Bassa HVDC Transmission Line

Abstract: High voltage transmission line design requires careful insulator selection to ensure good operational performance. This paper reports on the in-situ measurements of leakage current (LC) on composite and glass insulators of the Cahora Bassa high voltage direct current (HVDC) transmission line in South Africa over a 6month period. The influence of temperature, humidity, dew, rain and the HVDC line's voltage and current on LC are investigated. The results show that the composite and glass insulator LC behaviour i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
(22 reference statements)
2
5
0
Order By: Relevance
“…Notice that the leakage currents measured here are well above those reported by Meyer et al [12] and Roman et al [14]. This is because these insulators are polluted not only by NaCl, which is soluble and susceptible to humidity, but also by non-soluble iron oxides, such as Fe 2 O 3 , which are conductive even without humidity.…”
Section: Field Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Notice that the leakage currents measured here are well above those reported by Meyer et al [12] and Roman et al [14]. This is because these insulators are polluted not only by NaCl, which is soluble and susceptible to humidity, but also by non-soluble iron oxides, such as Fe 2 O 3 , which are conductive even without humidity.…”
Section: Field Resultssupporting
confidence: 79%
“…Although the humidity rises to almost 90%, no increase in leakage current was observed, confirming that in dry conditions, no LC occurs. Roman et al [14] concluded in their work that the LC increases from 0.01 mA to 0.08 mA when the humidity rises to up to 90% and the temperature drops to about 5 °C. By inputting these weather conditions in Equation ( 1), we find a dew point of 3 °C, which is below the local temperature; therefore, no humidity would accumulate on the insulator surface.…”
Section: Field Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, the increase in the temperature caused a decrease in the humidity, as well as in the leakage current. This result was therefore in line with [7][8][9]12]. Finally, Fig.…”
Section: Correlation On the Environmental Parameterssupporting
confidence: 87%
“…When applying a 19 kV voltage in lab tests, an average leakage current of about 6.5 µA was obtained, before the premature aging process of the silicone composite insulator tested [36], which is similar to that obtained for insulator 7 in table 4. Roman et al measured the leakage current in in-situ silicon composite insulators in a high-voltage direct current (HVDC) transmission line (400-500 kV) and obtained long-term values ranging from 10 to 60 µA [37]. The leakage current variability obtained in these studies may be associated with different test conditions, e.g., different applied voltages.…”
Section: Discussionmentioning
confidence: 99%